2013
DOI: 10.7763/ijesd.2013.v4.395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Forage Yield and Quality Traits among Proso Millet, Foxtail Millet and Sainfoin Varieties

Abstract: Abstract-In order to compare variation and relations among yield and quality traits of three forage species, 9 superior varieties of sainfoin (Onobrychis sativa), proso millet (Panicum miliaceum) and foxtail millet (Setaria italica), were assessed using complete block design with three replications. Results of ANOVA showed significant differences (p<0.01) among species in all factors. Although, the highest average values of 14.37 and 8.23 ton ha -1 Dry Matter (DM) yield were obtained for the foxtail and proso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Regarding this issue, Avcıoğlu et al (2009) stated that the yields in alfalfa changed depending on the varieties, climate, cultural procedures and the number of cuttings made during a season. In the studies conducted previously related to the salinity, it was also reported that the yield parameters varied among the forage species and its cultivars (Mlay et al 2006;Tavirimirwa et al 2012;Mohajer et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this issue, Avcıoğlu et al (2009) stated that the yields in alfalfa changed depending on the varieties, climate, cultural procedures and the number of cuttings made during a season. In the studies conducted previously related to the salinity, it was also reported that the yield parameters varied among the forage species and its cultivars (Mlay et al 2006;Tavirimirwa et al 2012;Mohajer et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Species and variety characteristics have an important effect on plant qualities (Arzani et al, 2001;Schut et al, 2010;Panahi et al, 2012). For example, in a study carried out by Mohajer et al (2013), which has been conducted to determine plant quality content of plants belonging to different and same species, all quality parameters among species and varieties are found to be significant. In other research, Vendramini et al (2010) have shown in a study conducted to determine yields and quality values of 9 warm-season forage grasses that qualitative and yield differences exist among species, and even among varieties belonging to the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers around the world have characterized diverse sainfoin germplasm using agro‐morphological traits and molecular markers, which are critical for sainfoin breeding (Bhattarai et al., 2018, 2017; Delgado et al., 2008; Mohajer, Jafari, et al., 2012; Mohajer et al., 2013; Zarrabian & Majidi, 2015; Zarrabian et al., 2013). In the Canadian context, Bhattarai et al.…”
Section: Sainfoin Breeding In Western Canadamentioning
confidence: 99%
“…Many researchers around the world have characterized diverse sainfoin germplasm using agro-morphological traits and molecular markers, which are critical for sainfoin breeding (Bhattarai et al, , 2017Delgado et al, 2008;Mohajer, Jafari, et al, 2012;Mohajer et al, 2013;Zarrabian & Majidi, 2015;Zarrabian et al, 2013). In the Canadian context, Bhattarai et al ( 2017) evaluated the genetic diversity of 38 sainfoin accessions that represented different regions of the world using five amplified fragment length polymorphism markers.…”
Section: Genetic Diversity and New Plant Introductionsmentioning
confidence: 99%